1990
DOI: 10.1520/jfs12812j
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Carboxyhemoglobin and Cyanide in Blood from Victims of the Dupont Plaza Hotel Fire in Puerto Rico

Abstract: Ninety-seven people died from a fire that occurred in the Dupont Plaza Hotel in Puerto Rico on 31 Dec. 1986. All, except four who died later in the hospital, were found dead at the scene. All of the fatalities at the hotel (except for eight) were burned beyond recognition. Blood from seventy-eight of the victims was screened for carboxyhemoglobin at the Institute for Forensic Sciences in Puerto Rico and was then sent to the National Institute of Standards and Technology, Gaithersburg, Maryland, for analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 7 publications
0
18
0
2
Order By: Relevance
“…Concentrations are reported on a mass basis because greater accuracy can be obtained from gravimetric measurements than is typically achievable with volumetric techniques. Working internal standard solutions containing 13 C 15 N mass fractions of ϳ3 g/g were prepared periodically by gravimetric dilution of the stock solution with 0.1 mol/L NaOH. The concentration of 13 C 15 N in the internal standard stock solution was calibrated by reverse ID MS against a standard solution of natural K 12 C 14 N. In this procedure, a known amount of natural CN is added to a weighed aliquot of the labeled internal standard solution, and the resulting mass ratio is measured in the GC/MS.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Concentrations are reported on a mass basis because greater accuracy can be obtained from gravimetric measurements than is typically achievable with volumetric techniques. Working internal standard solutions containing 13 C 15 N mass fractions of ϳ3 g/g were prepared periodically by gravimetric dilution of the stock solution with 0.1 mol/L NaOH. The concentration of 13 C 15 N in the internal standard stock solution was calibrated by reverse ID MS against a standard solution of natural K 12 C 14 N. In this procedure, a known amount of natural CN is added to a weighed aliquot of the labeled internal standard solution, and the resulting mass ratio is measured in the GC/MS.…”
Section: Methodsmentioning
confidence: 99%
“…Measured area counts at m/z 27 were corrected for endogenous 12 C 14 N in the blood and for the small amount of 12 C 14 N in the internal standard before construction of the regression line. The regression line was constructed by plotting the blank-corrected 27/29 peak-area ratio on the y axis and the ratio of the amount of 12 C 14 N standard to the amount of 13 C 15 N internal standard on the x axis. ANOVA at a 95% level of confidence indicated that the slopes and intercepts for the blood-based curves were not statistically different from those measured without the blood matrix.…”
Section: Linearitymentioning
confidence: 99%
See 1 more Smart Citation
“…Bu amaçla birçok yöntemler geliştirilmiştir. Zamanımızda ise düşük kon santrasyonda COHb tayini ve COHb'nin methemoglobin (MetHb), siyanmethemoglobin (CNMetHb) ve sulfhemoglobin (SHb) gibi diğer Hb bileşiklerinden ayrılması ile ilgili çalışmalara zamanımızda da Taşlan maktadır (4,5,12). Yukarda açıklanan yöntemlerle postmortem kan da saptanan COHb düzeyleri Tablo l'de gösterilmiştir.…”
Section: Discussionunclassified
“…In these studies, there is no significant correlation of reduced %COHb with measured blood cyanide concentrations [11][12][13][14]. In studies of individual events with large life loss Levin [15] found treating CO and HCN as additive useful in understanding the deaths that occurred while Birky et al [16] found that significant HCN concentrations were only found in victims that had fatal levels of CO. The prevailing methodology in toxic hazard analysis is to consider CO and HCN as additive through the use of an N-gas fractional effective dose model [5].…”
Section: Introductionmentioning
confidence: 99%